Penggunaan Bahasa Gaul (Slang) dan Implikasi Terhadap Nilai Karakter Pada Mahasiswa - Rismauly Septiana Sitorus; Lusia Oktaviani Br Tamba; Lili Tansliova (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Language serves as a medium of human communication as well as a unifying tool for the nation. Language is needed by everyone to express themselves, interact with others, and adapt to the environment. The existence of Indonesian language is negatively affected by the rise of slang. The purpose of this research is to 1) find out the types of slang use, 2) find out the implications of slang on student character values. The method used in this research is descriptive qualitative method. The results showed that students use slang, abbreviations in their daily communication which is a form of error in the use of Indonesian language properly and correctly. This can hinder the growth and development of Indonesian language which will have an impact on the loss of Indonesian language which is displaced due to slang in the future.